Birthweight, vitamin D receptor genotype and the programming of osteoporosis. - Dennison, E; Arden, N; Keen, R; Syddall, H; Day, I; Spector, T; Cooper, C (2001)
Studies of the association between polymorphisms of the gene for the vitamin D receptor (VDR) and adult bone mass have been inconsistent, pointing to the possibility that gene--environment interactions may vary in different populations. We have demonstrated previously an association between weight in infancy (a marker of the intrauterine and early post-natal environment) and each of adult bone mass and VDR genotype. We therefore sought to extend these observations in an elderly UK cohort and to investigate the possibility of an interaction between these genetic and early environmental markers of later osteoporosis risk. One hundred and sixty-five men and 126 women aged 61--73 years for whom birth records were available underwent bone mass measurements at baseline and follow-up 4 years later. Whole-blood samples were obtained, DNA extracted using standard techniques and polymorphisms in the VDR and collagen type I alpha 1 (Col IA1) genes identified. In the cohort as a whole, there were no significant associations between either birthweight or VDR genotype and bone mineral density (BMD) or bone loss rate at either site. However, the relationship between lumbar spine BMD and VDR genotype varied according to birthweight. Among individuals in the lowest third of birthweight, spine BMD was higher (P = 0.01) in individuals of genotype 'BB' after adjustment for age, sex and weight at baseline. In contrast, spine BMD was reduced (P = 0.04) in individuals of the same genotype who were in the highest third of the birthweight distribution. A significant (P = 0.02) statistical interaction was also found between VDR genotype and birthweight as determinants of BMD. Similar but slightly weaker associations were seen between lumbar spine bone mineral content (BMC) and VDR genotype in the lowest birthweight tertile. When examining the relationship between Col1A1 genotype and bone mass, lumbar spine BMC was higher in individuals of genotype 'Ss' or 'ss' in the lowest birthweight tertile (P = 0.02) after adjustment for age, sex and weight at baseline. These results suggest that genetic influences on adult bone size and mineral density may be modified by undernutrition in utero.